Public sector ethics : finding and implementing values - Sampford, C. J. G. (Charles J. G.); Preston, Noel, 1941-; Bois, C.-A. (Carol-Anne), 1960- (Federation Press ; Routledge, 1998)
This study, with contributions from both scholars and practitioners, examines the theory and practice of public sector ethics across a broad range of environments.
Keywords: Civil service ethics.; Public administration -- Moral and ethical aspects.; Public officers -- Professional ethics.; Political ethics.; Administrative agencies -- Moral and ethical aspects.; Public utilities -- Moral and ethical aspects.; Fonctionnaires -- Déontologie.; Administration publique -- Aspect moral.; Services publics -- Aspect moral.; Administration publique (Science) -- Aspect moral.; Morale politique.; POLITICAL SCIENCE -- General.; Civil service ethics; Political ethics; Public administration -- Moral and ethical aspects; Public officers -- Professional ethics; Beroepsethiek.; Ambtenaren.; Openbaar bestuur.